Cardio-metabolic disease genetic risk factors among Māori and Pacific Island people in Aotearoa New Zealand: current state of knowledge and future directions - Tony R. Merriman; Phillip L. Wilcox (Taylor & Francis Group, 2018)
Context: Cardio-metabolic conditions in Aotearoa New Zealand (NZ) Māori and non-indigenous Polynesian (Pacific) populations have been increasing in prevalence and severity, especially over the last two decades. Objectives: To assess knowledge on genetic and non-genetic risk factors for cardio-metabolic disease in the Māori and Pacific populations residing in Aotearoa NZ by a semi-systematic review of the PubMed database. To outline possible future directions in genetic epidemiological research with Māori and Pacific communities. Results: There have been few studies to confirm that risk factors in other populations also associate with cardio-metabolic conditions in Māori and Pacific populations. Such data are important when interventions are considered. Genetic studies have been sporadic, with no genome-wide association studies done. Conclusions: Biomedical research with Māori and Pacific communities is important to reduce the prevalence and impact of the cardio-metabolic diseases, as precision medicine is implemented in other Aotearoa NZ populations using overseas findings. Genuine engagement with Māori and Pacific communities is needed to ensure positive outcomes for genetic studies, from data collection through to analysis and dissemination. Important is building trust, understanding by researchers of fundamental cultural concepts and implementing protocols that minimise risks and maximise benefits. Approaches that utilise information such as genealogical information and whole genome sequencing technologies will provide new insights into cardio-metabolic conditions-and new interventions for affected individuals and families.